Development of a methacrylic acid-styrene co-polymer based QCM sensor to discriminate citronella essential oils relying on citronellol - Sumit Kundu; Tuhin Mallick; Deepam Gangopadhyay; Runu Banerjee Roy (Journal of Applied Research on Medicinal and Aromatic Plants, 2026)

3D reliability assessment of railway embankment under pore-water pressure and seismic loading using supervised machine learning models - Brijbhan Rao; Divesh Ranjan Kumar; Sumit Kumar; Warit Wipulanusat; Avijit Burman; Lal Bahadur Roy (Modeling Earth Systems and Environment, 2026)

Intensification of rice-wheat cropping system with summer green gram improves growth, productivity and profitability of rice in the middle Indo-Gangetic Plains of India - Manish Raj; Sushant; Mainak Ghosh; Anil Kumar Singh; Sumit Sow; Sanjay Kumar; Birendra Kumar; Swaraj Kumar Dutta; Nintu Mandal; Pritam Ganguly; Arnab Roy Chowdhury; Shishpal Poonia; et al. (European Journal of Agronomy, 2026)

Sediment load decline and increased erosion linked to human activities in the Cauvery delta, India - Sumit Das; Harshada Jadhav; Aditi Roy; Gianvito Scaringi (CATENA, 2025)

Investigation of MIL-53 (Fe)@Fe₃O₄ nanocomposites as sustainable catalysts for lignocellulose delignification in rice straw for biofuel applications - Anusha Rai; Ayan Singha Roy; Newton Roy; Lokesh Mane; Sai Suresh Hivarkar; Prashant K. Dhakephalkar; Sumit S. Dagar; Arpita Nandy (Bioresource Technology Reports, 2025)

Natamycin Cyclodextrin Supramolecular Complex Loaded Dissolvable Lenses for the Effective Management of Fungal Keratitis - Mabel Mascarenhas; Pinal Chaudhari; Lakshmi Sruthi Mallela; Sanhita Roy; Sumit Birangal; Vivek Ghate; Ananthamurthy Koteshwara; Jesil Aranjani; Arun K. Kodoth; Shaila A. Lewis (Journal of Pharmaceutical Innovation, 2025)

Influence of submergence ratio on scour morphology around spur dike: experimental and numerical analysis - Sai Guguloth; Abhimanyu Roy Chaudhuri; Niloufar Shafighi; Sumit Kumar (Acta Geophysica, 2025)

Source apportionment and risk assessment of heavy metals in mangrove soils using multivariate and sensitivity analyses - Annewsa Acharya; Debatri Dewanjee; Gourav Mondal; Shreya Chakraborty; Sonali Banerjee; Sumit Kumar; Saibal Ghosh; Riddhi Basu; Sumit Roy; Pradip Bhattacharyya (Journal of Environmental Chemical Engineering, 2025)

Uncovering deep trouble through multi-indices assessment: Geochemical fingerprints and human health risks of groundwater affected by coal mining - Sumit Kumar; Gourav Mondal; Vikas Sonkar; Shreya Chakraborty; Rupsha Nandi; Riddhi Basu; Debatri Dewanjee; Pankaj Kumar Roy; Pradip Bhattacharyya (Process Safety and Environmental Protection, 2025)

Prediction of thunderstorm evolution using deep learning models with doppler weather radar observations over southern part of India - Dharmadas Jash; Sumit Kumar; Arka Roy; E.A. Resmi; R.K. Sumesh; C.K. Unnikrishnan; Nita Sukumar (Dynamics of Atmospheres and Oceans, 2025)

Evaluating the impact of arbuscular mycorrhizal fungi on the phytoremediation potential of Vetiveria zizanioides and Saccharum spontaneum on coal mine waste, India - Sumit Kumar; Sonali Banerjee; Suvasri Dutta; Pankaj Kumar Roy; Pradip Bhattacharyya (Journal of Environmental Chemical Engineering, 2025)

Optimization of an Enhanced Micropropagation Protocol of Stevia rebaudiana for Mass Production in an Indian Sub-humid Region - K. Abha Manohar; Kasireddy Sivasankarreddy; Gopal Shukla; Moumita Chakraborty; Bidhan Roy; Sumit Chakravarty (Sugar Tech, 2025)

Extracellular Proteins of Pseudomonas bubulae KU04 as a Resource for Potent Antimicrobial Peptides Against Acinetobacter Baumannii and Pseudomonas aeruginosa - Rajendra Kr Roy; Raju Biswas; Rajdeep Shaw; Sumit Kumar Hira; Rajib Bandopadhyay (International Journal of Peptide Research and Therapeutics, 2025)

Customized Extrusion Nozzle Assisted Robust Nylon 6/MWCNT Nanocomposite Based Triboelectric Nanogenerators for Advanced Smart Wearables - Sunanda Roy; Barnali Dasgupta Ghosh; Sumit Mishra; Kheng Lim Goh; Jaehwan Kim (Chemical Engineering Journal, 2024)

Biochemical Responses in Zebra Fish (Danio rerio) on Acute Cadmium Exposure Under Temperature Variations - Dola Roy; Anisa Mitra; Bidisha Maitra Sen; Sumit Homechaudhuri (Proceedings of the Zoological Society, 2024)

Revealing soil microbial ecophysiological indicators in acidic environments laden with heavy metals via predictive modeling: Understanding the impacts of black diamond excavation - Sumit Kumar; Shreya Chakraborty; Saibal Ghosh; Sonali Banerjee; Gourav Mondal; Pankaj Kumar Roy; Pradip Bhattacharyya (Science of The Total Environment, 2024)

Modelling of hydrogen blending into the UK natural gas network driven by a solid oxide fuel cell for electricity and district heating system - Samiran Samanta; Dibyendu Roy; Sumit Roy; Andrew Smallbone; Anthony Paul Roskilly (Fuel, 2024)

Takeaways from the Recarbrio Conundrum: Has the FDA Jumped the Gun? - Riddhi Kundu; Sumit Roy Chowdhury (Indian Journal of Microbiology, 2023)

Examining TOD node typology using k-means, hierarchical, and latent class cluster analysis for a developing country - Md. Anwar Uddin; Sumit Roy (Innovative Infrastructure Solutions, 2023)

The Flower Colour Influences Spontaneous Nectaring in Butterflies: a Case Study with Twenty Subtropical Butterflies - Sumit Kumar Sinha; Avishek Dolai; Arjan Basu Roy; Sourav Manna; Amlan Das (Neotropical Entomology, 2023)

A non-destructive approach to develop tree-level allometric equations for estimating aboveground biomass in the forests of Tripura, Northeast India - Abhilash Dutta Roy; Sumit Kumar Das; Bimal Debnath (Tropical Ecology, 2023)

A mis-splicing early flowering 3 (elf3) allele of lentil is associated with yield enhancement under terminal heat stress - Anirban Roy; M. Hemakumar Reddy; Moutushi Sarkar; Diana Sagolsem; Sumit K. Murmu; Camellia Das; Debarati Roy; Shamba Ganguly; Rajib Nath; Prabir K. Bhattacharyya; Asutosh Sarker; Somnath Bhattacharyya (Journal of Applied Genetics, 2023)

Decision support system for sustainable groundwater management in crystalline hard rocks: implications for sugarcane agriculture, Southern India - Syed Adil Mizan; Sahebrao Sonkamble; Adarshya Sharadha; Md. Wajihuddin; Sumit Roy; Murli Dhar (Environmental Monitoring and Assessment, 2022)

A novel seasonal index–based machine learning approach for air pollution forecasting - Adeel Khan; Sumit Sharma; Kaushik Roy Chowdhury; Prateek Sharma (Environmental Monitoring and Assessment, 2022)

Fuelwood species diversity and consumption pattern in the homegardens from foothills of Indian Eastern Himalayas - Manish Roy; Biplov Chandra Sarkar; K. Abha Manohar; Gopal Shukla; Vineeta; Arun Jyoti Nath; Jahangeer A. Bhat; Sumit Chakravarty (Agroforestry Systems, 2022)

Rapid determination and optimisation of berberine from Himalayan Berberis lycium by soxhlet apparatus using CCD-RSM and its quality control as a potential candidate for COVID-19 - Anil Kumar Katare; Bikarma Singh; Pooja Shukla; Sandeep Gupta; Bishander Singh; Kavya Yalamanchili; Nitin Kulshrestha; Rajendra Bhanwaria; Ashok Kumar Sharma; Sarita Sharma; Sneha; Durga Prasad Mindala; et al. (Natural Product Research, 2022)

Comparative assessment of piscine beta diversity profile and key determinant environmental factors in two freshwater rivers of variable spatial scale in Dooars, West Bengal, India - Soumyadip Panja; Munmun Chakrabarty; Anupam Podder; Anwesha Roy; Missidona Biswas; Sumit Homechaudhuri (Tropical Ecology, 2021)

Differential Expression of Genes Responsible for Reproduction of Male and Female Danio rerio Following Interaction Between Estrogen Receptor and Cadmium - Dola Roy; Anisa Mitra; Sumit Homechaudhuri (Proceedings of the Zoological Society, 2021)

Automated mineralogical anomaly detection using a categorization of optical maturity trend at lunar surface - Sukanta Roy; Sumit Pathak; Subbaramajois Narasipur Omkar (International Journal of Remote Sensing, 2021)

Patterns of morphological traits shaping the feeding guilds in the intertidal mudflat fishes of the Indian Sundarbans - Anupam Podder; Soumyadip Panja; Atreyee Chaudhuri; Anwesha Roy; Missidona Biswas; Sumit Homechaudhuri (Journal of Fish Biology, 2021)
Broad‐scale patterns of resource utilization and the corresponding morphological evolution is a result of an integral relationship among form and function. In addition, there is also an inherent role of the latter in determining species co‐interaction and assemblage pattern that forms an integral aspect of ecological research. The present study aimed to evaluate the ecomorphological relationship among 37 fish species inhabiting the intertidal mudflats of the Indian Sundarbans by outlining the following objectives: (i) identifying and characterizing feeding guilds/groups and (ii) understanding the inter‐relationship between morphometry with (a) the established feeding guild classifications and (b) observed prey taxa (that characterizes these feeding groups) for determining the role of morphometry in prey acquisition followed by (iii) the evaluation of their potential phylogenetic convergence among the species. For the first objective, two approaches for feeding guild classification were made (3‐Guild and 8‐Guild) for assessing the prediction accuracy of morphological characters in identifying the different guilds. While the former was based on troph values, the latter classification mode relied on the similarities in diet composition among the different fish species. For addressing the second objective, we employed two different models namely, linear discriminant (LDA) and redundancy analysis (RDA). While the LDA model tested the prediction accuracy of morphological traits in classifying the different feeding guilds, RDA was applied to model the correlation between the morphological traits and the prey categories. In the LDA model, morphological characters showed higher accuracy (78.4%) in classifying three feeding groups rather than eight feeding groups (73%). Following this, the RDA model (explaining 79.78% of constrained variance) showed gill raker intensity, protrusion length, head depth, caudal peduncle, eye diameter and inter‐orbital distance to be highly associated with selection of specific prey types by species, thereby characterizing a particular feeding guild. However, generalized linear models testing for correlation between troph value and feeding groups showed substantial variation (90.35%) in the dietary index being explained by the 8‐Guild classification. Hence, our study maintains the assumption that broad morphological differentiation acts as one of the underlying processes resulting in dietary variations that results in the varying modes of resource utilization by the coexisting species, thereby determining the structure of a trophic guild. Furthermore, it also suggests that in terms of prey abundance or selectivity, the 8‐Guild model is much more conducive in representing the feeding habits of the species while the morphological traits reflected a relatively broader scheme of classification, ( i.e ., 3‐Guild model) with certain traits being phylogenetically conserved within these groups.

Variation in P-acquisition ability and acid phosphatase activity at the early vegetative stage of lentil and their validation on P-deficiency field - Shamba Ganguly; Anirban Roy; Sumit K. Murmu; Diana Sagolsem; Moutushi Sarkar; Shubhrajyoti Sen; Dibakar Das; Camellia Das; Prabir Chakraborty; Prabir K. Bhattacharyya; Rajib Nath; Kuldeep Tripathi; et al. (Acta Physiologiae Plantarum, 2021)

Analysis of genetic diversity of Colletotrichum population causing anthracnose in fruit crops using ISSR markers - Amrita Das; Buddhadeb Roy; Sumit Jangra; Amita Chowdhury; Deeba Kamil; T. Prameela Devi (Indian Phytopathology, 2021)

Variation in Population Characteristics and Harvesting Pressure Influencing Recruitment Pattern of an Economically Important Fish, Osteomugil cunnesius of Indian Sundarbans - Anwesha Roy; Sachinandan Dutta; Anupam Podder; Sumit Homechaudhuri (Proceedings of the Zoological Society, 2020)

Detection and Analysis of Coal Fire in Jharia Coalfield (JCF) Using Landsat Remote Sensing Data - Rakesh Kumar Mishra; Jai Krishna Pandey; Jitendra Pandey; Sumit Kumar; Paresh Nath Singha Roy (Journal of the Indian Society of Remote Sensing, 2020)

Evaluating Oxidative Stress in Labeo rohita, Infected Asypmtomatically with Native and Invasive Aeromonads Using Biochemical Indices - Dola Roy; Subharthi Pal; Sriparna Datta Ray; Sumit Homechaudhuri (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2019)

A Novel Method for Permeability Estimation from Micro-tomographic Images - Soumyadeep Paul; Sumit Roy; Pradyumna Ghosh; Mohammad Amin Faghihi Zarandi; Thomas Cender; Krishna M. Pillai (Transport in Porous Media, 2019)

Characterization of a bacterioferritin comigratory protein family 1-Cys peroxiredoxin from Candidatus Liberibacter asiaticus - Anamika Singh; Narender Kumar; Prabhat P. S. Tomar; Sumit Bhose; Dilip Kumar Ghosh; Partha Roy; Ashwani K. Sharma (Protoplasma, 2017)

Polymorphisms of CYP1A1, GSTM1 and GSTT1 Loci as the Genetic Predispositions of Oral Cancers and Other Oral Pathologies: Tobacco and Alcohol as Risk Modifiers - Sumana Chatterjee; Soujatya Dhar; Bani Sengupta; Ashish Ghosh; Manas De; Sumit Roy; Sila Chakrabarti (Indian Journal of Clinical Biochemistry, 2010)